Leading with local solutions to keep Yarrabah safe: a grounded theory study of an Aboriginal community-controlled health organisation's response to COVID-19 - Janya McCalman; Marlene Longbottom; Sara Fagan; Ruth Fagan; Suzanne Andrews; Adrian Miller (BMC, 2021)
Abstract Background Pandemics such as COVID-19 are a serious public health risk for Australian Aboriginal and Torres Strait Islander communities, yet primary healthcare systems are not well resourced to respond to such urgent events. At the start of the COVID-19 pandemic, a federal government advisory group recommended a rapid, tailored Indigenous response to prevent predicted high morbidity and mortality rates. This paper examines the efforts of one ACCHO, which in the absence of dedicated funding, pivoted its operations in response to COVID-19. Gurriny Yealamucka Health Service (Gurriny) is the only primary healthcare service in the discrete Indigenous community of Yarrabah, Far North Queensland. Methods The research was conducted at the request of the Chief Executive Officer of Gurriny. Using grounded theory methods, thirteen Gurriny staff and five Yarrabah and government leaders and community members were interviewed, transcripts of these interviews and 59 documents were imported into NVIVO-12 and coded, and key concepts were compared, organised into higher order constructs, then structured into a theoretical framework. Results Gurriny responded to COVID-19 by leading with local solutions to keep Yarrabah safe. Four key strategies were implemented: managing the health service operations, realigning services, educating and supporting community, and working across agencies. These strategies were enabled or hindered by five conditions: the governance and leadership capacity of Gurriny, relying on the health taskforce, locking the door, "copping it", and (not) having resources. A year after the first case was experienced in Australia and on the eve of vaccine rollout to Indigenous communities, there have been no COVID-19 cases in Yarrabah. Discussion The success of the locally led, holistic, comprehensive and culturally safe response of Gurriny suggests that such tailored place-based approaches to pandemics (and other health issues) are appropriate, but require dedicated resourcing. Key challenges were the fragmented and rapidly changing government processes, poorly coordinated communication and resource allocation channels, and bottlenecks in hierarchical funding approval processes. Conclusions The COVID-19 response in Yarrabah demonstrates the need for governance reform towards greater resourcing and support for local decision making by Aboriginal community-controlled health organisations.